Protein Kinase Serine/Threonine Kinase 24 Positively Regulates Interleukin 17-Induced Inflammation by Promoting IKK Complex Activation - Jiang, Yu; Tian, Miao; Lin, Wenlong; Wang, Xinyuan; Wang, Xiaojian (Frontiers in Immunology, 2018)
Interleukin 17 (IL-17) is a key inflammatory cytokine that plays a critical role in tissue inflammation and autoimmune diseases. However, its signaling remains poorly understood. In this study, we identified mammalian ste20-like kinase 3 (MST3) as a positive regulator of IL-17-mediated signaling and inflammation. MST3 deficiency or knockdown markedly inhibited IL-17-induced phosphorylation of NF-κB and impaired IL-17-induced chemokine and cytokine expression. MST3 overexpression greatly enhanced IL-17-induced NF-κB activation and expression of chemokines and cytokines in a kinase activity-independent manner. The IL-17-induced inflammatory response was significantly reduced in MST3 knockout mice. In addition, the severity of experimental autoimmune encephalomyelitis (EAE) was markedly reduced in mice with a loss of MST3 in non-hematopoietic cells. We further demonstrated that MST3 directly interacts with TAK1 and IKKβ and promotes the formation of TAK1 and IKK complexes, leading to enhanced IKKβ/NF-κB activation and downstream cytokine induction. Collectively, our findings suggest that MST3 plays an important role in controlling IL-17-triggered inflammation and autoimmune diseases and provides new insight into the therapeutic targets of IL-17-mediated inflammatory disease.